2014
DOI: 10.1002/er.3189
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a scroll expander for an organic Rankine cycle

Abstract: SUMMARY This paper presents experimental investigation of the performance of an organic Rankine cycle (ORC) with scroll expander which utilizes renewable, process and waste heats. An ORC test bench is built with a scroll expander‐generator unit modified from a refrigeration compressor‐electrical drive unit. A detailed experimental investigation within the test bench is performed with the organic working fluid R134a. The results show that scroll expander can effectively be used in low‐power ORC to generate mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…Oralli and Tarique investigate using a refrigeration scroll compressor as an expander for power generation applications using a Rankine cycle [35,36]. They develop a model applicable to using a scroll expander for determining the expansion process details, dissipation and leakage losses [36].…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Oralli and Tarique investigate using a refrigeration scroll compressor as an expander for power generation applications using a Rankine cycle [35,36]. They develop a model applicable to using a scroll expander for determining the expansion process details, dissipation and leakage losses [36].…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…They develop a model applicable to using a scroll expander for determining the expansion process details, dissipation and leakage losses [36]. Figure 2 is the system diagram of the model proposed by Tarique [36]. The model considers isentropic expansion, which is limited by the built in volumetric ratio.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to Equation (12), the electrical efficiency of the ORC system relates to the performance characteristics of the scroll expander. To evaluate the effects of resistive load on scroll expander isentropic and volumetric efficiencies, the investigation is carried out under the optimal pressure ratio operating condition for the six resistive loads.…”
Section: Variations Of Electrical Efficiency and Scroll Expander Effimentioning
confidence: 99%
“…Qiu et al [11] evaluated several expansion devices for micro-CHP ORC systems including turbine, scroll, screw and vane expanders, and suggested that both scroll and vane expanders are suitable for micro-scale ORC systems with capacity ranging from 1kW to 10kW. Ali Tarique et al [12] stated that a scroll expander is the best choice for small capacities due to the more flexible operation characteristic. As a scroll expander is a positive displacement machine with a fixed expansion ratio, a high efficiency could be achieved at a specific pressure ratio [13].…”
Section: Introductionmentioning
confidence: 99%